Effect of intermittent theta burst stimulation of the left DLPFC on cognitive function and inflammatory markers in post-stroke cognitive impairment: a randomized controlled trial - Xia, Jiayi; Chen, Yeping; Jiang, Xiaoyan; Pei, Song (Frontiers in Psychiatry, 2025)
ObjectiveTo evaluate the efficacy of intermittent theta-burst stimulation (iTBS) targeting the left dorsolateral prefrontal cortex (DLPFC) combined with cognitive training in patients with post-stroke cognitive impairment (PSCI), and to investigate its effects on systemic inflammatory biomarkers: homocysteine (Hcy), C-reactive protein (CRP), and lactate dehydrogenase (LDH).MethodsIn this single-center, randomized, sham-controlled trial, 69 PSCI patients received 4 weeks of daily cognitive training combined with either real iTBS (target: left DLPFC; 1200 pulses per session at 80 % of resting motor threshold, total 20 sessions) or sham stimulation. Assessments were conducted at baseline (week 0) and week 4, including measures of global cognition (Mini-Mental State Examination [MMSE], Montreal Cognitive Assessment [MoCA]), executive function (Frontal Assessment Battery [FAB]), activities of daily living (Barthel Index [BI]), domain-specific cognitive subscores (forward/backward digit span [FDS/BDS], delayed recall, attention), and inflammatory biomarkers (Hcy, CRP, LDH). Data were analyzed using two-way mixed General Linear Models (GLM) to assess main and interaction effects of Time and Group.ResultsSignificant Time effects were observed for all cognitive and biochemical measures (p < 0.001), indicating overall improvement after intervention. Significant Time × Group interactions favored the iTBS group for MMSE, MoCA, BI, FDS, BDS (p < 0.05), suggesting enhanced gains in global cognition, executive function, and working memory. Serum LDH showed a greater reduction in the iTBS group (p < 0.05), while decreases in Hcy and CRP were comparable between groups. Correlation analysis revealed that reductions in LDH and Hcy were significantly associated with improvements in MMSE, MoCA, FAB, and working-memory subscores in the iTBS group (r = −0.334 to −0.525, p < 0.05), supporting a metabolic-cognitive coupling effect.ConclusionsiTBS applied to the left DLPFC, combined with cognitive training, produces superior improvements in global cognition, executive function, and daily living ability compared with cognitive training alone in PSCI patients. The concomitant reduction in LDH suggests potential anti-inflammatory or neuroprotective mechanisms underlying these cognitive benefits. LDH may thus serve as a sensitive peripheral biomarker for neuromodulation-induced recovery in PSCI rehabilitation. Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2300076109.